Assessment of Rice Processing and Packaging Methods in New-Bussa, Niger State Nigeria - O. P. Olaifa; O. A. Akande; A. Sulyman; C. A. Iluyemi; A. S. Adedeji; A. Adetona (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to assess rice processing and packaging techniques amongst rice processors in New-Bussa and its environment, Niger State, Nigeria using appropriate standard procedures. Data obtained show that manual threshing method accounted for 62.0% while 71.0% use local parboiling method, 91.0% use mechanical milling. The drying method indicates that 82.0% uses sun drying method while 18.0% uses mechanical drier. The methods of Rice packaging indicates that majority (85.0%) of the respondents uses sack bag for packaging, 10.0% uses polythene bag while 3.0% uses bowl. The major constraints associated with Rice processing and packaging are poor access to institutional credits and inadequacy of modern storage and processing facilities with 29.0% and 22.0% each, followed by scarcity and high cost of inputs with 16.0% while the least constraints was uses of old milling machine (9.0%). The study concludes that rice processors were owned by an individual that could not afford modern machines for the production and processing of Rice in the study area. Therefore, the majority of these Rice processors were still using crude method of Rice processing and packaging.